Antibiotic Susceptibility Pattern of Escherichia Coli at Tertiary Care Hospital, Islamabad - Mehfooz, Ammar; Shaukat, Iqra; Qurat ul Ain; Begum, Shahzeera; Qureshi Hashmi, Mahe-Kamil; Khalid, Maryam (Indus Journal of Bioscience Research, 2024)
Objective: The objectives of this study are; 1. To comprehensively investigate the antibiotic susceptibility pattern of Escherichia coli, focusing on its virulence factors to understand its pathogenicity and address the challenges posed by antibiotic resistance. 2. To assess the prevalence of citrate and TSI in E. coli isolated from urine to evaluate the impact of antibiotics according to Clinical and Laboratory Standards Institute (CLSI 2023) guidelines. Study Design: Cross-sectional study. Study Place: Tertiary Care Hospital, Al Nafees Medical Hospital, Islamabad, Pakistan. Study Duration: March 2023 to October 2023. Methodology: Informed consent was obtained from the microbiology lab of Al Nafees Medical College. The study utilized biochemical tests, including citrate and TSI, for identification and differentiation of E. coli based on metabolic characteristics. A total of 50 urine samples were collected for isolation and identification of E. coli. The Kirby-Bauer disc diffusion technique was employed to determine antibiotic susceptibility, identifying nitrofurantoin and Fosfomycin as the most effective choices for bacterial infections. Results: Antibiotic efficacy assessments revealed nitrofurantoin as notably effective, surpassing other antibiotics according to CLSI guidelines. In contrast, ciprofloxacin demonstrated the lowest efficacy among the tested antibiotics. The research highlights the importance of judicious antibiotic selection for optimal therapeutic outcomes in clinical settings, emphasizing the need for continuous monitoring and optimization of antibiotic treatment strategies.